Enhancing photocatalytic hydrogen evolution by intramolecular energy transfer in naphthalimide conjugated porphyrins. Issue 82 (28th September 2018) - Bodedla, Govardhana Babu; Li, Lingling; Che, Yuanyuan; Jiang, Yijiao; Huang, Jun; Zhao, Jianzhang; Zhu, Xunjin
Abstract : Three new isomeric naphthalimide conjugated porphyrins are developed for photocatalytic H2 production. The para -substituted isomer, ZnT( p -NI)PP delivers the highest rate ( η H2 ) of 973 μmol g −1 h −1 due to the efficient intramolecular energy transfer from the naphthalimide to the porphyrin core. Abstract : Three new isomeric naphthalimide conjugated porphyrins, ZnT( p -NI)PP, ZnT( m -NI)PP andZnT( o -NI)PP are developed for photocatalytic H2 production. The para -substituted isomer, ZnT( p -NI)PP delivered a much higher H2 production rate ( η H2 ) of 973 μmol g −1 h −1 compared to that of meta - and ortho -substituted isomers, ZnT( m -NI)PP (597 μmol g −1 h −1 ) andZnT( o -NI)PP (54 μmol g −1 h −1 ), respectively. The ZnTPP produced η H2 of 7 μmol g −1 h −1, which is 200 times lower than theZnT( p -NI)PP . The highest η H2 ofZnT( p -NI)PP among the isomers could be attributed to the most efficient intramolecular energy transfer from the naphthalimide to the porphyrin ring which further enhanced the electron transfer from the photo-excited porphyrin moiety to the Pt co-catalyst.